Postharvest biological control of blue mold of apple by Pseudomonas fluorescens during commercial storage and potential modes of action - Wallace, Rhiannon L.; Hirkala, Danielle L.; Nelson, Louise M. (Postharvest biology and technology, 2017)
•Three P. fluorescens isolates inhibited P. expansum in vitro and in vivo.•Volatiles from P. fluorescens isolates completely inhibited spore germination.•Two P. fluorescens isolates showed potential for synthesis of phenazine.•Three P. fluorescens isolates colonized fungal hyphae in vitro and in apple wounds. Three Pseudomonas fluorescens isolates, 1–112, 2–28 and 4–6, isolated from the rhizosphere of pulse crops were tested for their ability to suppress Penicillium expansum (blue mold) on ‘McIntosh’ and ‘Spartan’ apples in commercial cold storage, and their possible mechanisms of action were investigated in vitro. On ‘McIntosh’ apples the decay incidence and lesion diameter of blue mold were significantly reduced by isolates 1–112 and 4–6 compared with control fruits after 15 weeks storage at 1°C. On ‘Spartan’ apples only isolate 2–28 provided significant levels of disease control after 15 weeks of storage at 1°C. In dual culture and in volatile tests all three isolates of P. fluorescens significantly inhibited conidial germination and mycelial growth of P. expansum in vitro. All three isolates were positive for the production of protease, but negative for cellulase, chitinase and glucanase. Molecular evidence for the potential for synthesis of the antibiotic, phenazine-1-carboxylic acid, in isolates 1–112 and 4–6 and of hydrogen cyanide in isolate 2–28 was obtained by polymerase chain reaction of phzCD and hcnBC genes, respectively. Genes for 2,4-diacetylphloroglucinol, pyoluteorin and pyrrolnitrin production were not detected in any of the P. fluorescens isolates. Scanning electron microscopy indicated that all three P. fluorescens isolates adhered to the fungal hyphae and colonized the wounds of apples, but only isolate 1–112 was able to colonize conidia of the fungal pathogen. P. fluorescens’ ability to compete for nutrients and space and produce inhibitory metabolites that target conidial germination and mycelial growth may be the basis for its control of P. expansum on apple.